PRODUCT DEVELOPMENT ON MSMEs IN LALADAN VILLAGE LAMONGAN REGENCY THROUGH DIGITAL LITERACY DURING THE COVID-19 PANDEMIC - MUHTAROM, ABID; BADRIYAH, NURUL; DJ, YUNNI RUSMAWATI; PURYANI, INDAH (The journal of contemporary issues in business and government, 2021)
The clustered community in Laladan Village, Lamongan District has a characteristic in making unsangrebon shrimp paste. During the pandemic, business actors experienced many problems, especially in the field of product marketing. Traditionally, the community and partners do not understand the true meaning and function of digital literacy. The method used consists of three stages, namely the preparation stage, implementation stage and mentoring. The results of the service activities that have been carried out by MSME Partners are that MSME actors are very enthusiastic about the digital literacy program.